Inovasi Pelayanan Publik Menggunakan Co Creation: Studi Kasus Kota Bandung - Aida Alfita; Banu Sulaeman Mubaraq; Noerma Kurnia Fajarwati (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
Public service is a motivation for the public. The existence of a public service can be a control over arbitrariness in the hands of policy makers. Innovation in public services helps the government further upgrade the conditions of its territory. Law No. 25 of 2009 concerning Public Services is a breath of fresh air in efforts to provide good public services. This law mandates that public service is an activity or series of activities in order to fulfill service needs in accordance with statutory regulations for every citizen. Public service innovation cannot be separated from community participation. Public service innovation is also used in Bandung where co-creation methods are used to improve public services. This method is used by the Bandung Dukcapil Office. The application of co-creation is a new breakthrough in data openness and also the accuracy of data from the government